Positive Psychotherapy-Based Family Education Program for Parents of Children Aged 0-6: Development and Application - Elif Bengi Unsal Ozberk (The Global Psychotherapist)
Positive Psychotherapy (PPT) provides a valuable framework for supporting family relationships by focusing on individuals' capacities, achieving balance across life domains, and harnessing the transformative potential of conflict. In response to the need for contemporary, attachment-oriented parent education programs, the Positive Psychotherapy-Based Family Education Program for Parents of Children Aged 0-6 was developed. The program consists of four sessions that address parent-child bonding, understanding and expressing emotions, building cooperation without relying on rewards or punishments, and fostering self-awareness in parents. Grounded in the theoretical principles of PPT, it aims to equip parents with knowledge and skills that align with the evolving needs of children and families today. A previous empirical study examining the effectiveness of the program demonstrated improvements in parenting self-efficacy and reductions in parental stress and authoritarian attitudes. This article presents the conceptualization, structure, and practical application of the Positive Psychotherapy-Based 0-6 Age Family Education Program, highlighting its contribution to modern practice within the framework of Positive Psychotherapy.